Numerical Simulation of Thermal Processes and the Effect of Heating of Near-Surface Layers of Titanium on the Diffusion Transfer of Dopants during High-Intensity Pulsed Ion Implantation; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17, iss. 6 - Ivanova A. I. Anna Ivanovna (2023, 2023)
Title screen